Open data: Frequency mismatch negativity and visual load - Stefan Wiens; Erik van Berlekom; Malina Szychowska; Rasmus Eklund (Stockholm University, 2018)
Wiens, S., van Berlekom, E., Szychowska, M., & Eklund, R. (2019). Visual Perceptual Load Does Not Affect the Frequency Mismatch Negativity. Frontiers in Psychology, 10(1970). doi:10.3389/fpsyg.2019.01970

We manipulated visual perceptual load (high and low load) while we recorded electroencephalography. Event-related potentials (ERPs) were computed from these data.

OSF_*.pdf contains the preregistration at open science framework (osf).
https://doi.org/10.17605/OSF.IO/EWG9X

ERP_2019_rawdata_bdf.zip contains the raw eeg data files that were recorded with a biosemi system (www.biosemi.com). The files can be opened in matlab with the fieldtrip toolbox.
https://www.mathworks.com/products/matlab.html
http://www.fieldtriptoolbox.org/

ERP_2019_visual_load_fieldtrip_scripts.zip contains all the matlab scripts that were used to process the ERP data with the toolbox fieldtrip. http://www.fieldtriptoolbox.org/

ERP_2019_fieldtrip_mat_*.zip contain the final, preprocessed individual data files. They can be opened with matlab.

ERP_2019_visual_load_python_scripts.zip contains the python scripts for the main task. They need python (https://www.python.org/) and psychopy (http://www.psychopy.org/)

ERP_2019_visual_load_wmc_R_scripts.zip contains the R scripts to process the working memory capacity (wmc) data. https://www.r-project.org/.

ERP_2019_visual_load_R_scripts.zip contains the R scripts to analyze the data and the output files with figures (eg scatterplots). https://www.r-project.org/.
Keywords: 170101 Biological Psychology (Neuropsychology, Psychopharmacology, Physiological Psychology); Neuroscience and Physiological Psychology; 170112 Sensory Processes, Perception and Performance; Neurosciences; Neurovetenskaper; Biological Sciences; Biologi